O aeroporto de Cuiabá na história regional : do “Campo Velho” ao novo aeroporto de Cuiabá em Várzea Grande (1929-1969) - Santos, Valmir Aparecido Ferreira dos (2013)
This dissertation is about the construction of the airport in Cuiaba between the decades 1930´s to 1960´s. The starting point is “Campo Velho”, Coxipó region, an area that, according to the documentation points, received the first plane that landed on the Cuiabá on March 28 Th, 1929. It then analyzes the Cuiabá River, in the time of seaplanes, between 1930´s and 1940´s, and “Campo de Aviação” - what is now the arm Village of military Cuiabá - during the same period, until the inauguration of the Cuiabá´s in Várzea Grande in 1956, and its operation in the 60'´s. As time frame were used balisas is 1929´s and 1969´s. The first indicates the first arrival of an aircraft at capital of Mato Grosso, in the second one reveals Cuiabá in time of jet planes.The research makes a flyover in the history of the capital city of the state of Mato Grosso in this period, and identifies the main creators of the project of construction of the airport of Cuiaba in regional history, which was supported by a discourse of modernization, by Cuiabá-Várzea Grande economic elite, political and literate elite throughout the twentieth century.